2016
DOI: 10.1007/s41134-016-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Human Rights and Social and Economic Justice: Developing Competence in Field Education

Abstract: Social workers advance human rights and social and economic justice through their practice and policy work. The Council on Social Work Education (CSWE) mandates that social work students develop knowledge, values, and skills in this area, as one of the core competencies of their professional training. This qualitative study analyzed learning contracts of four cohorts of BSW seniors (n = 114) to identify the stated activities for advancing human rights and social and economic justice through field education. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Learning agreements, commonly individualized, are used to plan learning opportunities, connect field work to the classroom, and serve as a basis for evaluation to ensure core competencies are met (Tapp, 2012). Davis and Reber (2016) found that if social work graduates are to advance human rights, it is important to develop the human rights-related competencies through meaningful learning agreement activities and responsibilities. The authors concluded that as students developed skills, they became better equipped to align with the mission of the profession.…”
Section: Human Rights In Social Work Education and Practicementioning
confidence: 99%
“…Learning agreements, commonly individualized, are used to plan learning opportunities, connect field work to the classroom, and serve as a basis for evaluation to ensure core competencies are met (Tapp, 2012). Davis and Reber (2016) found that if social work graduates are to advance human rights, it is important to develop the human rights-related competencies through meaningful learning agreement activities and responsibilities. The authors concluded that as students developed skills, they became better equipped to align with the mission of the profession.…”
Section: Human Rights In Social Work Education and Practicementioning
confidence: 99%
“…Twenty-two of the 32 articles contains suggestions for how to integrate human rights into social work education (Acquaye & Crewe, 2012;Barbera, 2006;Chiarelli-Helminiak et al, 2018;Davis & Reber, 2016;Gammonley et al, 2013;Gardella, 2000;Hawkins & Knox, 2014;Hodge, 2007Hodge, , 2010Kaiser et al, 2015;Lewis et al, 2016;McPherson & Cheatham, 2015;McPherson & Mazza, 2014;Melekis & Woodhouse, 2015;Nesmith & Smyth, 2015;Patterson, 2004;Reichert, 2011b;Richards-Desai et al, 2018;Steen & Mathiesen, 2005;Steen et al, 2017;Witkin, 1994Witkin, , 1999. Many of the articles provided examples or case studies where a human rights integration model was used.…”
Section: Pedagogical Framework Models and Examplesmentioning
confidence: 99%
“…With field education designated as the signature pedagogy for social work, field placements also provide an ideal opportunity for students to contextualize their work at agencies through a human rights framework (Barbera, 2006;Davis & Reber, 2016;Lewis et al, 2016;Steen et al, 2017). In this context, students can hear of the experience of practicing social workers, gain professional skills, and begin to apply human rights concepts to practice settings.…”
Section: Integration Into Existing Courses and Curriculamentioning
confidence: 99%
See 1 more Smart Citation
“…This means altering the curricula to include not only an understanding of what human rights are and what it means, but to create opportunities to integrate these concepts into the field education (McPherson and Cheatham, 2015;Werkmeister Rozas and Garran, 2016). Through development of human rights competency, social workers will develop the passion, motivation, and experience to effect change and enact the mission of the profession (Davis and Reber, 2016).…”
Section: Implications For Social Work Educationmentioning
confidence: 99%